Workplace monitoring in the Radiation Physics and Metrology Laboratory (LAF-RAM) - Andrea Castillo; Josselyn Mendoza; Norma Roas (Brazilian Journal of Radiation Sciences)
The values of environmental equivalent dose H*(10) using thermoluminescent dosimeters (TLD) in the Radiation Physics and Metrology Laboratory (LAF-RAM) from 2019 to 2021 are presented. Fifteen measuring points are monitored on a total of 23 monitoring periods. The selected locations include the public areas, the supervised areas. The characterization of the environmental dosimetry of LAF-RAM was possible finding no significative variations in the temporal evolution of the evaluated periods and the results do not indicate any risk to occupational workers or members of public.